LOSS OF RAR-RELATED ORPHAN RECEPTOR ALPHA (RORα) SELECTIVELY LOWERS DOCOSAHEXAENOIC ACID IN DEVELOPING CEREBELLUM - Chen, Chuck T (Prostaglandins Leukot Essent Fatty Acids, 2019)
Deficiency in retinoid acid receptor-related orphan receptor alpha (RORα) of staggerer mice results in extensive granule and Purkinje cell loss in the cerebellum as well as in learned motor deficits, cognition impairments and perseverative tendencies that are commonly observed in autistic spectrum disorder (ASD). The effects of RORα on brain lipid metabolism associated with cerebellar atrophy remain unexplored. The aim of this study is to examine the effects of RORα deficiency on brain phospholipid fatty acid concentrations and compositions. Staggerer mice (Rora(sg/sg)) and wildtype littermates (Rora(+/+)) were fed n-3 polyunsaturated fatty acids (PUFA) containing diets ad libitum. At 2 months and 7 or more months old, brain total phospholipids fatty acids were quantified by gas chromatography-flame ionization detection. In the cerebellum, all fatty acid concentrations were reduced in 2 months old mice. Since total fatty acid concentrations were significantly different at 2-month-old, we examined changes in fatty acid composition. The composition of ARA was not significantly different between genotypes; though DHA composition remained significantly lowered. Despite cerebellar atrophy at >7-months-old, cerebellar fatty acid concentrations had recovered comparably to wildtype control. Therefore, RORα may be necessary for fatty acid accretions during neurodevelopment. Specifically, the effects of RORα on PUFA metabolisms are region-specific and age-dependent.